Highly Luminescent and Scintillating Hybrid Halide of (C13H25N)2[MnBr4] Enabled by Rigid Cation - Renfu Li; Lulu Jiang; Qinghua Zou; Jianlong Bai; Lingkun Wu; Jianrong Li; Jinsheng Liao (Molecules)
Organic–inorganic hybrid manganese halides (OIMnHs) have attracted significant attention in the field of optoelectronics due to their outstanding optical properties and low toxicity. However, the development of crystalline compounds with scintillating properties and high light yield remains a significant challenge. In this study, a simple solution method was employed to successfully synthesize a new zero-dimensional (0-D) scintillation crystal, (C13H25N)2[MnBr4] (C13H25N = trimethyladamantan-1-aminium). The introduction of bulky and rigid organic cations not only spatially isolates the [MnBr4]2− tetrahedrons but also effectively expands the Mn···Mn distance, thereby suppressing the concentration quenching and self-absorption effects. This structural design achieves a high photoluminescence quantum yield of about 63.8% at room temperature and a remarkable light yield of 44,300 photons MeV−1. After multiple irradiation cycles, the material retains its stable radiative characteristics. This work highlights the key role of rigid cation engineering in improving luminescence efficiency and scintillation performance and provides new ideas for designing efficient and nontoxic OIMnH-based scintillators.